Декоративні персики в умовах степової Наддніпрянщини - Kabar, A.N.; Shoferistov, Ye.P.; Opanasenko, V.F.; Plotnikova, T.N. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
It is marked that the plants selected and studied hybrids forms F2 between nectarine and almond are characterized by different level of resistance to Sphaerotheca pannosa (Lév.) var. persicae Woronich., Taphrina deformans (Berk.) Tul., Clasterosporium carpophilum (Lév.) Aderh., Monilia cinerea Bonord. The perspective genotypes have been selected for using in breeding work and nursery practice.